När det inte räcker att säga förlåt: En argumentationsanalys av ursäkten som avståndstagande - Larsson,Philip (2013)
This thesis puts light onto, and criticizes, the view of an apology or an excuse as an end or a goal in itself instead of as an on going project with further implications. My ambition is to in this thesis introduce and detect the weaknesses with the arguments in mainstream discussion and theories and give an alternative interpretation of the concept apology. My conclusion, in short, is that even if the ambition and the excuse is explicitly good it implicit something more problematic sometimes even polemic arguments. Instead I suggest seeing the apology not just as recognition of the oppression but also recognition of the victim and the consequences of the oppression. I came to this conclusion with help of multiple theories, mainly through a reading of phenomenologists represented by Franz Fanon, a posthuman reading of the humanism, and probably most importantly the poststructural theories and especially Judith Butler and Jacques Derrida.
Keywords: erkännande; humanism; förtryck; skuld; ursäkt